Correction: Scaffold mediated gene knockdown for neuronal differentiation of human neural progenitor cells. (2nd May 2019) - Chooi, Wai Hon; Ong, William; Murray, Aoife; Lin, Junquan; Nizetic, Dean; Chew, Sing Yian
Abstract : Correction for 'Scaffold mediated gene knockdown for neuronal differentiation of human neural progenitor cells' by Wai Hon Chooi et al., Biomater. Sci., 2018, 6, 3019–3029.